Learning Media of PPT-iSpring with Macroscopic, Submicroscopic and Symbolic Representations for Improvement of Chemistry Teacher Competency - Zulhendra Zulhendra (Pelita Eksakta, 2022)
Activities of Community service in scheme of Program Kemitrasaan Masyarakat (PKM) aim to improve the competence of high school and vocational high school chemistry teachers in Pariaman Regency in making PPT-iSpring learning media which have macroscopic, submicroscopic and symbolic level. PKM methods are lectures, demonstrations and workshops. The lecture method is used to convey ICT and internet terminology, three levels of chemistry representation and 21st century learning. The demonstration method is to download general chemistry e-books and chemistry learning videos and workshops for making PPT-iSpring learning media. This activity can improve the knowledge and skills of chemistry teachers using various learning resources from websites, teachers' knowledge of the three levels of representation and their interconnections, chemistry teachers' knowledge and skills in combining chemistry learning resources to be used in making PPT-iSpring learning media based on ICT with an emphasis on macroscopic, submicroscopic and symbolic level representation.